Driving performance of retinitis pigmentosa patients. Issue 2 (February 1981) - Fishman, G A; Anderson, R J; Stinson, L; Haque, A
Abstract : The driving performance of 42 patients with retinitis pigmentosa (RP) was compared with that of 87 control subjects. Although the patients with RP were involved in more isolated road accidents than the control group, 50% were not involved in any accident over the most recent 5-year driving period. When the associations between driving performance and case/control status were examined (the number of driving hours per week and driving years being taken into account), differences in the number of accidents between the 2 groups were significant because of a disproportionately high number of accidents caused by a subgroup of female RP patients. No significant correlations were apparent between central visual efficiency or peripheral field efficiency and number of road accidents.